Influence of system pressure on gas–solid reactions for thermochemical energy storage in a suspension reactor - Lena Schmieder; Sandra Jezernik; Simon Gatt; Noah Steinacher; Franz Winter (Energy Conversion and Management: X)
Thermochemical energy storage using salt hydrates is a promising approach to store medium to low-temperature heat, but previously investigated reactor designs often suffer from poor heat and mass transfer, inhomogeneous moisture distribution or particle agglomeration. This study examines the effect of system pressure on suitable solid–gas reactions in a novel three-phase suspension reactor that aims to solve these problems. The reversible dehydration reactions of CaCl2·2H2O, H3BO3, K2CO3·1.5H2O and CuSO4·5H2O were investigated under vacuum (≥ 50  mbar) and pressurised conditions (≤ 8 bar) using liquid water for hydration. Dehydration onset temperatures were reduced by 33–66 °C (e.g., CuSO4·5H2O: 105 °C → 57 °C), with dehydration rates increasing up to 2.1 times compared to ambient pressure. All four materials demonstrated stable performance over five charging-discharging cycles without particle agglomeration. Hydration experiments for K2CO3 and CuSO4·H2O at up to 8  bar showed mostly pressure-independent reaction rates, with CuSO4·H2O exhibiting increased temperature lift at higher suspension temperatures. These findings demonstrate that system pressure control in suspension reactors can significantly reduce charging temperatures and charging time, and improve operational flexibility of the technology, supporting its scale-up for seasonal or industrial heat storage applications.